APLIKASI MOBILE PADA SENTRA INDUSTRI SENI PATUNG DAN UKIR DI DESA MULYOHARJO UNTUK MENINGKATKAN POTENSI PASAR - Nur Aeni Widiastuti (Computer Society of Nahdlatul Ulama (CSNU) Indonesia, 2018)
Mulyoharjo is the center of wood sculpture and sculpture industry which is included in Jepara regency, Central Java. Mulyoharjo is now developed into a tourist village of creative industries that began to favor a lot of local and foreign tourists. Mulyoharjo has excellent potential such as sculpture or wood carving. Local tourists and foreign tourists need information about the carving industry in Mulyoharjo to be visited. But to find the carving industry in Mulyoharjo is still limited in the website that takes a long time in the search process. So to know the carving industry information is less effective and efficient. Utilization of the progress of smartphone technology is one solution to this problem. Therefore, researchers apply an information-based android mobile app that provides information about the potential of existing industries in Mulyoharjo Village, based on location/map. Development method used in making this application is waterfall method using the ionic framework which is devoted to building a hybrid mobile application with HTML5, AngularJS, and CSS. The development of this application in the form of images, data and map location is included into the firebase database so that application renewal becomes young, fast and efficient. Based on the assessment by the respondents as a whole, the New Jepara application scored 81.3% with criteria very feasible to use.Keywords: Mobile application, waterfall method, carving industry center.